Tri Hita Karana-Based Thematic Teaching Materials on the Topic of Clean, Healthy, and Beautiful Environment - Gede Dharmawan Gede Dharmawan; I Made Candiasa; I Gede Astawan (Universitas Pendidikan Ganesha, 2023)
The lack of thematic teaching materials provided by schools and the government encourages teachers to focus on learning that does not refer to local wisdom, and the materials used are not contextual. Responding to this phenomenon, this study aims to develop Tri Hita Karana-based thematic teaching materials for grade 1 elementary school students. This type of research is developed using the ADDIE model. The methods used to collect data are observation and questionnaires. The instrument used to collect data is a questionnaire. The research subjects were learning material experts and learning media experts. The test subjects were students totaling 10 people. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results of the study, namely the results of the validity test, were declared valid with a Content Validity Coefficient of 1. Thematic teaching materials also met the practicality criteria with a score of 4.9 in the very practical category. Based on the trial, it was found that the teaching materials were very effective, with an average student score of 88 with 90% completeness. It was concluded that teaching materials in the form of Tri Hita Karana-based Thematic Teaching Materials for a clean, healthy, and beautiful environment are appropriate and effective for use in learning.